The City of Murcia through the Analysis Proposed by the Geography of Perception and Behavior: A Dialectic between Rational and Emotional Space - Morales-Yago, Francisco José; Lázaro y Torres, María Luisa de (Revista de Estudios Andaluces, 2018)
The analysis and use of the interior space of the city is conditioned not only by economic and social factors, but also by the images or mental representations that people make of the places where they live or know through sources of information that exist. Mental imagery is influenced by the paths used in the journeys, the places that are frequented and the feelings of identification or rejection with the space object of daily use. We present the results of a significant sample of surveys (M = 215) and of the mental maps elaborated to know the perception of the city of Murcia by its inhabitants. Based on the results, proposals will be sought for improvement that contribute to the harmonious and sustainable growth of the city, correcting palpable deficiencies that may alter the quality of life in it.